Utilization of organic farming practices and materials by small scale farmers in Ogun State Nigeria (2014)
In Nigeria several small scale farmers make use of organic materials such as compost and manure to maintain soil organic matter and as sources of nutrients. The advantages of organic farming could include increased productivity and enhanced biodiversity of the farm lands and surrounding environment. This paper examined the utilization of organic of practices and materials, with highlight on farmers' demographics, knowledge of organic farming, attitude and constraint to use of organic practice and materials among small scale farmers' in Nigeria. The population consisted of all crop organic farmers registered with the agricultural departments then random sampling procedure was used to select 141 farmers in the study area. The data collected were analyzed with the aid of descriptive statistical tools while the hypotheses was tested using Pearson Product Moment Correlation (PPMC). Findings reveal that about half (50.4%) of the farmers were aged 51-60 years of age. While only (7.1% and 1.4%) were less than 30 years and above 60 years respectively. majority of the farmers were Christian (75%) adults (50.4%), males (86.5%), and married (78%) and own 1-2 acres of farm land (92.2%). The result showed there was high level of use of organic farming practice and materials among small scale farmers in Ogun State, as utilization of organic practice of management of soil fertility, Pest and disease control was high. It can be concluded that knowledge (r= 0.468, p = 0.002) affect the use and practice of organic agriculture leading to favourable attitude which also affected (r = 0.187, P = 0.026) the use of organic farming.